Hematological and Biochemical Alterations in Patients with Recurrent Aphthous Stomatitis: Hematological Alterations in Patients with Recurrent Aphthous Stomatitis - Batool, Sarwat; Dall, Abdul Qadir Khan; Naeem, Aqsa; Memon, Mahwish; Waqas, Madiha; Shaikh, Khalida (Pakistan Journal of Health Sciences, 2025)
Recurrent aphthous stomatitis (RAS) is a common oral mucosal disorder characterized by painful, recurring ulcers. Its etiology remains multifactorial, with potential links to hematological and biochemical imbalances. Objectives: To compare the hematological and biochemical profiles of adult patients with and without recurrent aphthous stomatitis (RAS) attending the outpatient department of a teaching hospital in Hyderabad, Pakistan. Methods: A total of 130 participants were enrolled using a non-probability convenience sampling method, with 65 individuals in the RAS group and 65 healthy controls. Standardized clinical oral examinations were conducted to evaluate the presence, number, and location of ulcers in RAS patients, while controls were examined to confirm the absence of oral mucosal lesions. Under sterile conditions, 6 mL of blood was collected from each participant for hematological and biochemical analyses, including serum levels of cortisol, ferritin, iron, folic acid, and vitamin B12, measured using an auto-analyzer. Results: Independent t-tests revealed significantly higher cortisol levels in RAS patients (459.2 ± 49.6 nmol/L) compared to controls (232.4 ± 119.4nmol/L, p=0.001). Conversely, ferritin, iron, and folic acid levels were significantly lower in the RAS group (p=0.001). Hemoglobin (12.9 ± 2.1g/dL vs 14.0 ± 1.4g/dL, p=0.001) and hematocrit (37.88 ± 8.14% vs 40.85 ± 5.81%, p=0.018) were also significantly lower in RAS patients, while differences in RBC, WBC, and platelet counts were not statistically significant. Conclusions: These findings suggest potential connections between RAS and altered specific biochemical and hematological markers, including cortisol, ferritin, iron, folic acid, hemoglobin, and hematocrit.